Behavior of Listeria innocua Strains Under Pressure Treatment – Inactivation and Sublethal Injury - Justyna Nasiłowska; Barbara Sokołowska; Monika Fonberg-Broczek (Polish Journal of Food and Nutrition Sciences)
The inactivation and sublethal injury of two strains of Listeria innocua (one collection strain and one wild strain isolated from beetroot juice) suspended in beetroot juice and in model solutions, after high hydrostatic pressure (HHP) were investigated. Changes within the population assessed by plating count methods of both L. innocua strains suspended in a buffer pH 4.0 were more noticeable than in the natural beetroot juice environment. In beetroot juice the lethal effect was reported after 1 min of pressure treatment at 400 MPa for the collection strain. In the case of the wild type strain, exposure to the maximal parameters of the compression process (400 MPa, 10 min) decreased the population number below 1 log (CFU/mL) but did not cause complete injury. The collection strain of L. innocua was easier to inactivate in beetroot juice than the strain isolated from this environment. The maximum level of sublethal injury was observed when the cells were suspended in a buffer pH 7.0. Structural damage in cell membranes after HHP processing was observed using a transmission electron microscope (TEM).